Customer Relationship Management : Literature Review - Rafikah Zulyanti, Noer; Rizal Nur Irawan, Mohamad (International Journal of Science, Technology & Management, 2023)
The purpose of this article is to provide a more meaningful view of CRM starting from the CRM definitions of several figures along with their orientation and the CRM strategic model framework so that later they can contribute to researchers and companies about CRM implementation and show that by managing customer relationships with both can increase the value of the organization/company. The method used is a literature study derived from previous books and articles that analyze the CRM model. There are 10 models in this article that are presented with comprehensive discussions and reviews that explore customer-centric, technology solutions to improve customer relationships, knowledge management systems, employee involvement in organizational performance.